1996
DOI: 10.1002/(sici)1097-0215(19960529)66:5<653::aid-ijc12>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine stimulation of AR4-2J rat pancreatic tumor cell growth by glycine-extended gastrin

Abstract: Glycine-extended gastrin (gastrin-Gly) stimulates proliferation of AR4-2) pancreatic tumor cell line through a specific receptor, different from the gastrin-cholecystokinin B receptor. Our purpose was to determine whether AR4-2) cells produced gastrin-Gly and then whether the peptide was involved in an autocrine loop. First, proliferation of AR4-2) cells in serum-free medium was inhibited by a gastrin anti-sense oligodeoxynucleotide phosphorothioate and by antibodies specific for gastrinGly. In contrast, antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…There are, however, substantial amounts of G17-Gly generated in rat antrum; the data suggest that this material should be regarded as an end product in its own right. This conclusion is interesting in the context of recent reports that -Gly-extended gastrins might have characteristic biological activities, notably stimulation of cell growth and of proton pump gene expression, independent of those of the amidated gastrins (12)(13)(14).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There are, however, substantial amounts of G17-Gly generated in rat antrum; the data suggest that this material should be regarded as an end product in its own right. This conclusion is interesting in the context of recent reports that -Gly-extended gastrins might have characteristic biological activities, notably stimulation of cell growth and of proton pump gene expression, independent of those of the amidated gastrins (12)(13)(14).…”
Section: Discussionmentioning
confidence: 68%
“…However, recent reports indicate that gastrins extended at the COOH terminus by glycine also have biological actions, notably growth. promoting effects on the AR4-2J cell line and stimulation of H+/K+ ATPase a-subunit gene expression, that are distinct from those of the amidated gastrins and appear to be mediated by novel receptors (12)(13)(14). Peptides terminating in gastrins with COOH-terminal glycine (-Gly)' are converted to COOHterminally amidated peptides by the enzyme, peptidyl a-amidating mono-oxygenase (PAM) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Two gastrin peptides were compared; gastrin-17 (G17), the form involved in endocrine pathways and GlyG17, a form secreted by tumor cells themselves and ascribed a role as an autocrine factor (20). It was confirmed that both G17 and GlyG17 increased tubule formation of human endothelial cells grown on an extracellular matrix and enhanced HB-EGF expression and shedding.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of specific gastrin proteins secreted by tumor cells, Goetze et al (7), using a specific radioimmunoassay, confirmed amidated gastrin expression in 14 of 19 carcinomas, whereas a second study detected mainly precursor gastrin forms, progastrin and glycineextended gastrin (8). Glycine-extended gastrin peptides were also shown to be secreted by the rat pancreatic adenocarcinoma cell line AR42J (14).…”
Section: Introductionmentioning
confidence: 99%